The Effect of Price Perceptions, Service Quality, Promotion and Consumer Value on Satisfaction - Zain, Efendy; Fadillah, Erlita Nur (SAN Scientific, 2025)
This study examines the impact of cost perception, service quality, innovation, and customer value on Xiboba customer satisfaction in DKI Jakarta, viewed from an Islamic perspective. The research employs purposive sampling, with 200 respondents surveyed using a questionnaire. Data analysis is conducted through multiple linear regression. The results indicate that (1) cost perception has a positive and significant effect on customer satisfaction, (2) service quality positively and significantly influences customer satisfaction, (3) innovation has a positive and significant impact on customer satisfaction, and (4) customer value also plays a crucial role in satisfaction. Furthermore, (5) collectively, cost perception, service quality, innovation, and customer value significantly affect Xiboba’s customer satisfaction. These independent variables contribute to the dependent variable. Managerial implications highlight the need for businesses to focus on competitive pricing, enhancing service quality, implementing unique innovative strategies, and delivering clear added value to customers. Aligning with Islamic business ethics, emphasizing fairness in pricing, service excellence, and ethical innovation is essential for achieving and maintaining optimal customer satisfaction.